Vocabulary Learning Strategies in First-Year International Undergraduate Students - Gutierrez Marenco, Darwin (English Lecturers and Teachers Association (ELTA), 2025)
The learning development of a second language is one of the major challenges for foreign and second language learners. This challenge expands more when these learners find themselves in an academic setting as international students in English-speaking countries such as the USA. This research study explores significant literature on remarkable factors that assist students in developing their vocabulary. It also investigates the learning strategies that a group of international undergraduate students from Southern Illinois University Edwardsville put into practice to foster and expand their English vocabulary repertoire. A mix of both qualitative and quantitative methods were used to collect and analyze data to answer the various questions that arise in regard to the experience and strategies students use in formal and informal settings when applicable. This study confirms two hypotheses: one suggests that first language influences second language vocabulary acquisition, while the other indicates that understanding word meanings through context positively impacts vocabulary learning. Other strategies such as online interactive exercises, dictation, memorization, and real-life examples were also identified, although they have a slightly lesser impact compared to those that support the hypotheses. Keywords : Vocabulary learning, L1 interference; EFL learning; vocabulary strategies